The impact of urbanization on flood in Klang Valley / Nur Nasuhah Abdullah - Abdullah, Nur Nasuhah (2020)
Changes in land use associated with urban development affect flooding in many ways. Removing vegetation and soil, grading the land surface, and constructing drainage networks increase runoff to streams from rainfall and snowmelt. Flash foods are common phenomena in the capital city of Malaysia. Every year, the city experiences several flash floods and Klang Valley is one of the worst-hit flash flood district affected by the flood. This research aimed at determine the impact of urbanization and land changes on flood in Klang Valley which focused at the Mass Rapid Transit (MRT) area, three MRT station that were chosen is MRT Batu Sebelas Cheras (SBK 30), MRT Bukit Dukung (SBK 31), MRT Sungai Jernih (SBK 33). The data set that was used in this study is Landsat 5 (TM) and Landsat 8 (OLI) satellite image, this image is used in land classification for year 2010, 2014 and 2018 as this study starts at the pre development of MRT, during development of MRT and post development of MRT. Rainfall data is also used in order to calculate the surface runoff, rational method was used in calculating the runoff by using other parameter such as runoff coefficient and catchment area. The Land changes analysis and Rainfall-runoff analysis were done in this research study.